Changing Fire Governance in Gabon′s Plateaux Bateke Savanna Landscape - Gretchen Marie Walters (Conservation & Society, 2015)
In many African savannas, anthropogenic fire regimes are changing for reasons that are poorly understood. However, these changes will likely impact landscapes. Using the case of the Teke-Alima people of Gabon′s savannas, the transition from communal, annual hunting fires, organised by land chiefs, to semi-annual, hunting fires lit by individuals is explored through a fire governance analysis. The centralisation of authority over natural resources with the state was key in changing the fire regime in the 1960s. This shift resulted from the reduction of customary authority over fire use and was compounded by the introduction of guns, population movements, and the rise of the Bateke elite. Today, the state is considering co-management of some areas, and fire is being used to manage landscapes created by historic fire governance. Understanding the past regimes that created the current landscape, and engaging with the people who are still part of the remnant customary system will be critical for shaping future management decisions.